Relative position of mandibular foramen for inferior alveolar nerve block in children: A digital panoramic radiographic study - Upadhyay, Sumita; Poudyal, Sijan; Mahanta, Swagat Kumar; Bali, Harleen; Luitel , Abhinaya; Niroula, Deepa (Journal of Kathmandu Medical College, 2021)
Background: For a successful inferior alveolar nerve block, good knowledge of position of mandibular foramen is imperative. Objectives: To evaluate the position of mandibular foramen in relation to mandibular occlusal plane and anterior border of ramus in a selected population of children in Nepal using digital panoramic radiographs. Methods: An analytical cross-sectional study was done after ethical approval in convenient sample of 180 children of 3-13 years in department of Paediatric and Preventive Dentistry, Dhulikhel Hospital from January 2021 to August 2021. Their digital panoramic radiographs were analysed using software Rainbow TM Image Viewer version 1.0.0.0. Mean with standard deviation were calculated for linear measurements taken from mandibular foramen to mandibular occlusal plane and deepest point on the anterior border of ramus. Paired t-test was used to compare measurements between right and left sides. Student t-test was used to evaluate the difference between boys and girls. Pearson correlation was used to observe the correlation of age with the linear measurements. Results: The mean linear measurements increased along with the increase in age (p <0.05). There was statistically significant difference in linear measurements between the two sides of mandible except in 3-4 years children for mandibular foramen to anterior border of ramus which was not significant (p = 0.090). There was no significant difference in linear measurements between boys and girls. Conclusion: For inferior alveolar nerve block, the needle should be placed below the occlusal plane in children up to seven years of age and above for higher ages.